1999
DOI: 10.1002/(sici)1097-4571(1999)50:3<207::aid-asi3>3.3.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

A theory of life in the round

Abstract: This study addresses ways in which inmates at the only maximum-security prison for women in Neuse City (in the northeastern United States) redefine their social world in order to survive incarceration. An aim of the project is to engage in theory building in order to examine the experiences of a world that is "lived in the round." A life in the round is a public form of life. It is a lifestyle with an enormous degree of imprecision. Yet, it is this inexactitude that provides an acceptable level of certainty. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 22 publications
2
65
0
3
Order By: Relevance
“…Different from constraints related to social stigma and cultural taboo, small-world related barriers are confined to certain local communities that are relatively closed to outsiders. Retirement houses (Chatman, 1992) and prisons (Chatman, 1999) exemplify well small-world communities of this kind.…”
Section: Small-world Related Barriersmentioning
confidence: 91%
See 3 more Smart Citations
“…Different from constraints related to social stigma and cultural taboo, small-world related barriers are confined to certain local communities that are relatively closed to outsiders. Retirement houses (Chatman, 1992) and prisons (Chatman, 1999) exemplify well small-world communities of this kind.…”
Section: Small-world Related Barriersmentioning
confidence: 91%
“…Drawing on the ideas of Chatman (1991Chatman ( , 1996Chatman ( , 1999, such constraints are referred to as small-world related barriers. Different from constraints related to social stigma and cultural taboo, small-world related barriers are confined to certain local communities that are relatively closed to outsiders.…”
Section: Small-world Related Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Robbin (1984) and Siegel (1981a, 1981b) found that the highly bureaucratic decision making structures of state agencies and perceptions of the external environment strongly influenced decisions that staff made to release or deny access to administrative records containing confidential information. Chatman's (1999) study shows how the walls of a state prison constrain the world view of its women inmates. Organizational hierarchies influenced how information systems were designed and later implemented (Kling & Jewett, 1995;Kling, Kraemer, Allen, Bakos, Gurbaxani, & Elliott, 1996;Napier & Smith, 2000).…”
Section: Discussion: Locating Explanation In Theories Of the Social Lmentioning
confidence: 99%